ASUHAN KEBIDANAN PADA IBU BERSALIN DAN BAYI BARU LAHIR DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Miftahussa’adah; Mei Munawwarah (Jurnal Kesehatan Husada Gemilang, 2021)
Childbirth is the process of removing the results of conception (fetus, placenta, and amniotic fluid) from the uterus to the outside world through the birth canal or other ways with the help or with the mother's own strength. In Indragiri Hilir Regency the Maternal Mortality Rate (MMR) is 9 people and the Infant Mortality Rate (IMR) is 21 people. The important factor in efforts to reduce the mortality rate is a clean and safe normal delivery and following established procedures. The purpose of this care is to be able to provide midwifery care for maternity mothers and newborns Mrs. “R” G3 P2 A0 H2 at the Bunda Puja Maternity Home. This care was carried out on July 1, 2019. This care uses Varney's 7-step management which is documented in SOAP form. From the results of midwifery care for pregnant women and newborns Mrs. "R" G3 P2 A0 H2 there is no gap between theory and practice in the field. It is hoped that health workers can improve the quality of health services, especially in providing midwifery care for maternity and newborns and follow Normal Delivery Care (APN) training in order to renew knowledge in accordance with their development.